2016
DOI: 10.1128/aac.01275-16
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Genome-Editing Platform for Drug-Resistant Acinetobacter baumannii Reveals an AdeR-Unrelated Tigecycline Resistance Mechanism

Abstract: bInfections with the Gram-negative coccobacillus Acinetobacter baumannii are a major threat in hospital settings. The progressing emergence of multidrug-resistant clinical strains significantly reduces the treatment options for clinicians to fight A. baumannii infections. The current lack of robust methods to genetically manipulate drug-resistant A. baumannii isolates impedes research on resistance and virulence mechanisms in clinically relevant strains. In this study, we developed a highly efficient and versa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 43 publications
2
60
0
Order By: Relevance
“…In previous investigations, coexistence of these two amino acid substitutions have been detected in both tigecycline resistant isolates, like our results, and tigecycline susceptible ones; hence, their detailed effect is in debate [3,4,6,14]. [17]. Tigecycline non-susceptibility can occur as a result of synergistic contribution of AdeIJK with AdeABC [10], while AdeABC has superior in uence [18,38].…”
Section: Discussionsupporting
confidence: 73%
“…In previous investigations, coexistence of these two amino acid substitutions have been detected in both tigecycline resistant isolates, like our results, and tigecycline susceptible ones; hence, their detailed effect is in debate [3,4,6,14]. [17]. Tigecycline non-susceptibility can occur as a result of synergistic contribution of AdeIJK with AdeABC [10], while AdeABC has superior in uence [18,38].…”
Section: Discussionsupporting
confidence: 73%
“…Deletion of nalC and single nucleotide mutations in pmrB and mexZ were introduced in P. aeruginosa PA14 based on a two-step recombination method previously described ( Trebosc et al 2016 ). DNA fragments corresponding to 700-bp up- and downstream of the nalC region to be deleted (position 1,391,565–1,390,977 on PA14 genome, GenBank CP000438.1) were amplified by PCR using primers oVT464/oVT465 and oVT466/oVT467, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…AdeABC is the superfamily of efflux pumps responsible for aminoglycoside resistance. Gene targeted therapy for the gene Ade-R, which regulates AdeABC, was examined as a possible solution to tigecycline resistant A. baumannii; however, the results were not promising, indicating that Gram-negative bacteria like A. baumannii likely have multiple mechanisms of resistance to tigecycline [38]. Use is now falling out of favor while cure rates are dropping in comparison with carbapenems such as imipenem, as well as a higher mortality rate when compared to colistin [17].…”
Section: Tigecyclinementioning
confidence: 99%
“…Although the knock-out of Ade-R was successful, the isolates still remained largely multi-drug resistant, indicating other mechanisms of resistance likely exist. The research still showed that this kind of genome editing can be used to study and manipulate MDR and XDR bacteria [38].…”
Section: Other Therapeutic Approachesmentioning
confidence: 99%